Analysis of Export Value, Capita Expenditure, and Inflation Against Economic Growth - Zulfahmi Syahputra Nasution; Hasan Basri Tarmizi; Muhammad Syafii (BIRCU, 2021)
Economic growth is an indicator that is often used for economic conditions in developing countries like Indonesia. Growing the economy of a region can be done by increasing economic activities in the area. This research was conducted with the aim of seeing and showing the effect of export value, inflation and per capita expenditure on economic growth in North Sumatra. The research was conducted using quantitative methods using data from 1990 to 1999 based on the variables used in the variables in this study. Export value and per capita expenditure have an effect on Economic Growth in North Sumatra Province. The value of the results of the comparative test or t-test conducted shows that the variable export value has a value of 2.826 and 2.323 so that there is an influence that affects economic growth. Meanwhile, inflation does not have a significant effect on Economic Growth in North Sumatra Province. Based on the t-test, the output of the inflation variable gets a value of -8,431, so it can be stated that economic growth in North Sumatra cannot occur positively on inflationary activity in North Sumatra.